Development of an unmanned aerial vehicle - Tay, Liang Kiat. (2012)
The deployment of unmanned aerial vehicle (UAV) has gained under acceptance in the last few years as the technology has advanced and the role and capability of UAV have expanded. Mission planners have become more concerned about sending humans to areas that pose a great danger to them.